Ocena wymywalności i biodostępności metali ciężkich w popiele przemysłowym z biomasy = Evaluation of leaching and bioavailability of heavy metals from industrial biomass ashes - Koniuszy-Nycz, Justyna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The purpose of the study was to evaluate the total content, leachability and bioavailability of Fe, Zn, Cu, Cr, Cd, Pb, Ni, Co in industrial ashes obtained from biomass combustion. It was found that metals occur in the test material as: macronutrient - iron (0,67 %), micronutrients - zinc (335,0 mg/kg), nickel (145,0 mg/kg), lead (110,0 mg/kg), copper (100,0 mg/kg), cobalt (25,0 mg/kg), chrome (15 mg/kg) and trace amount of cadmium (10,0 mg/kg).
Keywords: ekstrakcja sekwencyjna; popiół z biomasy; frakcjonowanie; ashes from biomass; sequential extraction; fractionation